2020
DOI: 10.1002/jcc.26150
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous polymerization of nitrogen in compressed cupric azide

Abstract: Metal azides have attracted increasing attention as precursors for synthesizing polymeric nitrogen. In this article, we report the amorphous polymerization of nitrogen by compressing cupric azide. The ab initio molecular dynamics simulations show that crystalline cupric azide transforms into a disordered network composed of singly bonded nitrogen at a hydrostatic pressure of 40 GPa and room temperature. The transformation manifests the formation of a π delocalization along the disordered Cu‐N network, thus res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…5 systematically illustrates the relationship between energy density and nitrogen content of stable binary nitrogen-rich and polymeric nitrogen compounds at room temperature. 6,9,13–16,18–20,30,33,40–62 Notably, the energy density increases with the increasing nitrogen content. Researchers have spent much endeavors to synthesize nitrogen-rich compounds with nitrogen content >75%, and these compounds mainly consist of light cations and nitrogen anions.…”
Section: Resultsmentioning
confidence: 98%
“…5 systematically illustrates the relationship between energy density and nitrogen content of stable binary nitrogen-rich and polymeric nitrogen compounds at room temperature. 6,9,13–16,18–20,30,33,40–62 Notably, the energy density increases with the increasing nitrogen content. Researchers have spent much endeavors to synthesize nitrogen-rich compounds with nitrogen content >75%, and these compounds mainly consist of light cations and nitrogen anions.…”
Section: Resultsmentioning
confidence: 98%
“…For divalent covalent azides M(N 3 ) 2 (M = Cu, Hg, Pb), it is generally agreed that the longest N1-N2 bond breaks first, forming N 3 MN radicals and N 2 , and then N 3 MN radicals are decomposed into N 2 and metal nitride [16][17][18]. In addition, it is found that crystalline cupric azide transforms into amorphous state where the N-N bond lengths is close to that of polymeric nitrogen at 40 GPa through ab initio molecular dynamics simulation [19]. However, the above studies are based on the periodic bulk crystal of copper azide, the decomposition mechanism on azide surfaces is still unclear and may be different from the mechanism of bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Azides are a kind of energetic materials, which exhibit a rich variety of important industrial and military applications that have been widely used in initial explosives, combustibles, and propellants. , In particular, under the influence of external stimuli (such as pressure or temperature), azides are regarded as the promising precursors in the synthesis of polynitrogen compounds, a new generation of high energy density materials (HEDMs) which would release a large amount of stored chemical energy. Previous experimental studies have shown that the azide ions of sodium azide can transform into amorphous-like clusters then into polymeric nitrogen nets above 120 GPa . In addition, several theoretical studies on inorganic azides indicate that the azide ions could be turned into benzene, like N 6 rings or zigzag N chains, and then forming polymeric nitrogen at sufficiently high pressure. , The high polymerization pressure in inorganic azides is caused by the linear azide ion that the hybridization of electron orbit is difficult to occur between adjacent nitrogen atoms .…”
Section: Introductionmentioning
confidence: 99%